Cryptography Generator for Prevention SQL Injection Attack In Big Data - Martiano Martiano; Yoshida Sary (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2022)
Currently, especially in Indonesia, data leaks occur in domestic agencies and private e-commerce. From these problems, cryptographic researchers are needed to make the data difficult to read, this research forms cryptography through a substitution method which will determine the number of keys that have been used and generated back in the dictionary, in its implementation the researcher uses the Devops design method, this method uses 4 stages, namely 1. ) continues development, 2) continues testing, 3) continues integration, 4) continues development. The results obtained by the text can be encrypted and described perfectly and successfully as much as 15864 data, and consumes low resources